Guidance of Sex Education for Pre-Puberty Children: Study at Darul Muttaqein Bogor - Norhayati Binti Khalil; Imas Kania Rahman (Prophetic guidance and counseling journal, 2022)
Sex education is a comprehensive education that needs to be disclosed publicly to pre-puberty-children aged between 7 to 10 years old. To ensure that they understood the meaning of life and are not being affected by western ideology. Providing sex education in Islam is very important to find their true identity and understand the concept of life as a Muslim when they reached puberty. This article aims to find out knowledge taught to pre-puberty age children about sex education. This research used qualitative methods, combining library researched (pedagogies aspect) and field researched (psychologist aspect). The results showed that the guidance of sex education about the body anatomy and their relevance to faith, worship, and sharia is to ensure that the child understands their responsibility and to adopt good morals in life. Abstrak         Pendidikan seks merupakan pendidikan komprehensif yang perlu didedahkan kepada anak pra-akil baligh berumur antara 7 hingga 10 tahun. Ini memastikan mereka memahami erti kehidupan dan tidak terpengaruh dengan ideologi Barat. Menyediakan pendidikan seks dalam Islam adalah penting untuk mencari identitas kebenaran mereka dan memahami konsep kehidupan sebagai seorang Muslim apabila mereka mencapai usia akil baligh. Tujuan artikel ini adalah untuk mengetahui apa yang diajar kepada kanak-kanak umur pra-akil baligh tentang pendidikan seks. Kaedah kualitatif digunakan dalam penyelidikan ini dengan menggabungkan penelitian perpustakaan (aspek paedegogis) dan penyelidikan lapangan (aspek psikologi). Hasil kajian menunjukkan bimbingan pendidikan seks mengenai anatomi tubuh dan kaitannya dengan iman, ibadah dan syariat adalah untuk memastikan anak memahami tanggungjawab mereka dan menyesuaikan akhlak yang baik dalam kehidupan